Pertumbuhan vegetatif anggrek Dendrobium stratiotes Rchb.f. setelah pemberian monosodium glutamat dan pupuk “Hortech” - Nintya Setiari; Yulita Nurchayati (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Fertilizers are needed to encourage the growth of orchids because their growth is known to be very slow. Monosodium glutamate (MSG) is a crystalline salt containing sodium and glutamate which can stimulate plant growth. Therefore in this study, the application of MSG and fertilizer was carried out to promote the growth of D. stratiotesorchids. The application of MSG and fertilizer was given in a completely randomized design with a factorial pattern consisting of MSG concentration factors (0, 0.5 and 1%) and fertilizing factors (not fertilized and fertilized). There are six treatments and three replications per treatments. The parameters observed increased in leaf length (cm), the morphological response of orchid plants in the form of new shoot formation, new root formation, and bulb enlargement. Results of research and test Analysis of Variance (ANOVA) showed no interaction between MSG and fertilizer in influencing the length leaf orchid D. stratiotes. The length of leaves is highest in orchids by MSG 1% without fertilizer, while the formation of new shoots and bulb enlargement occurred in orchid plants which were given 0.5 and 1% MSG without fertilizer application. New root formation occurs in plants given MSG and fertilizer. The conclusion is the application of 1% MSG without fertilizer can promote the growth of. D. stratiotesorchids.